A look around inheritances and drifts of the Grounded Theory - Federico Abiuso; Matías Alcántara (Perspectivas Metodológicas​)
Our main goal with this article is to carry out a reflective exercise regarding the theoretical-methodological strategy known as Grounded Theory (GT), with no exhaustiveness or generalization intended. The writing is schematically divided in two sections. The first segment describes GT's characteristics as presented in social sciences' introductory books on qualitative research methodology. At the next fraction, we will be resuming Argentinian, Spaniard and Chilean texts where the specific uses and applications of this research strategy tools are disclosed. We firmly believe this reflexive-comparative exercise contributes to the GT's various returns, uses and appropriations.